On Post–Apocalyptic and Doomsday Prepping Beliefs: A New Measure, Its Correlates, and the Motivation to Prep. Issue 4 (July 2019) - Fetterman, Adam K.; Rutjens, Bastiaan T.; Landkammer, Florian; Wilkowski, Benjamin M.
Post–apocalyptic scenarios provide the basis for popular television shows, video games, and books. These scenarios may be popular because people have their own beliefs and visions about the apocalypse and the need to prepare. The prevalence of such beliefs might also hold societal relevance and serve as a type of projective test of personality. However, there are no quantitative accounts of post–apocalyptic or prepping beliefs. As such, we conducted seven studies ( N total = 1034) to do so. In Studies 1 and 2, we developed a post–apocalyptic and prepping beliefs scale, explored its correlates, and confirmed its structure and psychometric properties. In Study 3, we attempted to activate a 'prepper' mindset and further explore the correlates of the new scale. In Studies 4 and 5, we investigated covariations in daily feelings, thoughts, and events, and prepping beliefs. In Studies 6a and 6b, we compared scores from 'real' preppers and to a non–prepping group. Overall, we found that post–apocalyptic concerns and prepping beliefs are predictive of low agreeableness and humility, paranoia, cynicism, conspiracy mentality, conservatism, and social dominance orientation. We also found that increased belief in the need to prep is associated with God–belief, negative daily experiences, and global political events. © 2019 European Association of Personality Psychology